Debris buster is a Drosophila scavenger receptor essential for airway physiology. - Wingen, A.; Carrera, P.; Ekaterini Psathaki, O.; Voelzmann, A.; Paululat, A.; Hoch, M. (Developmental Biology, 2017)
Scavenger receptors class B (SR-B) are multifunctional transmembrane proteins, which in vertebrates participate in lipid transport, pathogen clearance, lysosomal delivery and intracellular sorting. Drosophila has 14 SR-B members whose functions are still largely unknown. Here, we reveal a novel role for the SR-B family member Debris buster (Dsb) in Drosophila airway physiology. Larvae lacking dsb show yeast avoidance behavior, hypoxia, and severe growth defects associated with impaired elongation and integrity along the airways. Furthermore, in dsb mutant embryos, the barrier function of the posterior spiracles, which are critical for gas exchange, is not properly established and liquid clearance is locally impaired at the spiracular lumen. We found that Dsb is specifically expressed in a group of distal epithelial cells of the posterior spiracle organ and not throughout the entire airways. Furthermore, tissue-specific knockdown and rescue experiments demonstrate that Dsb function in the airways is only required in the posterior spiracles. Dsb localizes in intracellular vesicles, and a subset of these associate with lysosomes. However, we found that depletion of proteins involved in vesicular transport to the apical membrane, but not in lysosomal function, causes dsb-like airway elongation defects. We propose a model in which Dsb sorts components of the apical extracellular matrix which are essential for airway physiology. Since SR-B LIMP2-deficient mice show reduced expression of several apical plasma membrane proteins, sorting of proteins to the apical membrane is likely an evolutionary conserved function of Dsb and LIMP2. Our data provide insights into a spatially confined function of the SR-B Dsb in intracellular trafficking critical for the physiology of the whole tubular airway network.